Does Breathing Every Two Cycles Reduce the Breaststroke Energy Cost? - Alves, Miriam Natacha; Monteiro, Ana Sofia; Fernandes, Ricardo J.; Barbosa, Tiago M.; Vilas Boas, Joao Paulo (International Journal of Sports Medicine, 2025)
World Aquatics rules require only part of the swimmer’s head to break the surface each breaststroke cycle. We aimed to assess the impact of breathing every one or two cycles in breaststroke on energy cost (C) and related bioenergetic variables. Fifteen swimmers completed a 6-week intervention to learn the new breathing pattern, followed by a 5×200-m step test (0.05-m∙s−1 increments, 30-s rest) in both patterns. Oxygen consumption (VO2) and blood lactate ([La−]) were measured to calculate energy expenditure (Etot) and C. Linear and exponential regressions were computed between Etot and velocity. Paired t-tests and ANCOVA were applied, controlling for World Aquatics points and age. [La−] peak, VO2 peak, Etot, and C were lower at some intensities when breathing every cycle. Adjusted analyses showed higher Etot with breathing every two cycles at steps 1, 2, and 5. Linear and exponential regressions showed strong associations for both breathing patterns (r2=0.74 vs. 0.72, respectively). Individual regressions showed similar patterns in some swimmers, while others differed. Breathing every two cycles elicited higher bioenergetic responses at steps 1, 2, and 5 and did not prove effective during incremental 200-m efforts when compared to the traditional breathing pattern.
Keywords: oxygen consumption; lactate concentration; performance